WATER LEVEL PROFILE IN PARIT BERKAT DRAINAGE CHANNEL OF PUNGGUR BESAR - Riandini, Alfi; Nurhayati, Nurhayati; Soeryamassoeka, S.B. (Fakultas Teknik Universitas Tanjungpura, 2023)
Floods are common natural catastrophes in Indonesia, particularly during the rainy season. The Parit Berkat water catchment region is one of the locations that frequently experience flooding. The channel's capacity must be increased to accommodate the current water discharge, resulting in this condition. Several reasons are responsible for the diminished capacity of the canal. For instance, inhabitants' activities along canal banks might contribute to the siltation of channels. This research aimed to evaluate the influence of tides and rainfall on the flow of the Parit Berkat Canal. This research provided the use of both primary and secondary data. The leading information consists of measurements of the cross-section and length of the channel and the elevation of the tidal water level over 15 days. Secondary data consists of the maximum daily rainfall data received from Balai Wilayah Sungai Kalimantan I (BWSK I) and the location map for the research. The flow profile is simulated using HEC-RAS. The findings demonstrate that when maximum rainfall and low tides coincide, 13 stations are safe in the 2-year return period of rain, eight stations are safe in the 5-year return period, and six stations are safe in the 10-year return period.